Gut microbiota of elite female football players is not altered during an official international tournament. (19th November 2021) - Oliveira, Catarina B.; Marques, Cláudia; Abreu, Rodrigo; Figueiredo, Pedro; Calhau, Conceição; Brito, João; Sousa, Mónica
Abstract : The current study aimed to investigate if the gut microbiota composition of elite female football players changes during an official international tournament. The study was conducted throughout ten consecutive days, encompassing seven training sessions, and three official matches. The matches were separated by 48–72 h. Seventeen elite female football players from the Portuguese women's national football team participated in the study. Fecal samples were collected at two time points: at the beginning and end of the tournament. Fecal microbiota was analyzed by sequencing the 16S rRNA gene. Throughout the study, the duration and rating of perceived exertion (RPE) were recorded after training sessions and matches. The internal load was determined by the session RPE. The gut microbiota of players was predominantly composed of bacteria from the phyla Firmicutes (50% of relative abundance) and Bacteroidetes (20%); the genera Faecalibacterium (29%) and Collinsella (16%); the species Faecalibacterium prausnitzii (30%) and Collinsella aerofaciens (17%). Overall, no significant changes were observed between time points ( p ≥ 0.05). Also, no relationship was found between any exercise parameter and the gut microbiota composition ( p ≥ 0.05). These findings demonstrate that the physical and physiological demands of training and matches of an official international tournament did not change the gut microbiota composition of elite female football players. Furthermore, it supports that the gut microbiota of athletes appears resilient to the physical and physiological demands of training and match play.